Factors influencing provider deviation from national HIV and nutritional guidelines for HIV-exposed children in western Kenya: a qualitative study - Megan M. Coe; Emily Yoshioka; Damaris Odhiambo; Mary Masheti; Phlona Amam; Julius Nyaoke; Emmanuel Oduor; Marline Serede; Agnes Ndirangu; Benson Singa; Arianna Rubin Means (BMC Health Services Research)
Abstract Background Malnutrition and HIV interact in a vicious cycle for HIV-exposed infants (HEIs), increasing vulnerability and the severity of each condition and contributing to poor health outcomes. We identified multi-level factors influencing provider adherence to Kenyan HIV and nutrition guidelines for HEIs. Methods We conducted six focus group discussions and seven in-depth interviews using a semi-structured question guide. Participants were selected through purposive maximum variation sampling of health workers involved in maternal and child health services and outpatient nutrition programs at two facilities in western Kenya. Data collection and analysis were guided by the Theoretical Domains Framework (TDF). Transcripts were coded by two primary coders using both deductive and inductive thematic analysis. Results TDF domains that drove guideline adherence included: environmental context and resources, beliefs about capabilities, and social influences. While participants praised attempts to integrate HIV and nutritional services through teamwork and service colocation, challenges in the successful referral of patients between services persisted. Participants described siloed HIV and nutrition-related knowledge across staff, leading to missed or delayed care if certain providers were unavailable. Participants emphasized understaffing as a major contributor to gaps in care. Inconsistent material resource availability also disrupted linkages between HIV and nutrition services for patients. While participants frequently expressed high intention and internal motivation to link children between services, they described minimal structured supervision or positive reinforcement from supervisors and feeling demoralized when resource constraints interfered with care provision. Lastly, participants described patient-level factors that made it challenging for families to seek or remain in care, including poverty and HIV and malnutrition-related stigma. Participants made several recommendations, including training multiple cadres in the fundamentals of both HIV and nutritional care to address siloed services and understaffing. Conclusions This study details the factors that facilitate or hinder health workers as they implement national guidelines and link HEIs between HIV and nutritional services, including the impact of physical integration of service sites, human and material resource constraints, and health worker motivation. Future interventions can address these challenges by expanding access to needed resources, task sharing, and testing implementation strategies that increase the efficiency of service delivery to improve linkages in care for vulnerable infants.